2016
DOI: 10.1186/s12864-016-3186-0
|View full text |Cite
|
Sign up to set email alerts
|

Dwarfism with joint laxity in Friesian horses is associated with a splice site mutation in B4GALT7

Abstract: BackgroundInbreeding and population bottlenecks in the ancestry of Friesian horses has led to health issues such as dwarfism. The limbs of dwarfs are short and the ribs are protruding inwards at the costochondral junction, while the head and back appear normal. A striking feature of the condition is the flexor tendon laxity that leads to hyperextension of the fetlock joints. The growth plates of dwarfs display disorganized and thickened chondrocyte columns. The aim of this study was to identify the gene defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…As a core transcription factor in embryonic stem cells, ZNF281 (zinc finger protein 281) was found to be related to spontaneous osteochondrogenic differentiation [38]. Other studies showed the strong association of LCORL/NCAPG, HMGA2, PROP1, LASP [39], ZFAT, DIAPH3 [40], ACTN2, ADAMTS17, GH1, ANKRD1 [40], and ACAN [41,42] with miniature size and dwarfism in a variety of pony breeds, including Shetland [41,43], miniature [44], Welsh ponies [45], German warmblood horses [46], American miniature horses, Brazilian ponies [47], and Jeju ponies [48], as well as B4GALT7 [49] and PROP1 [50] in Friesian horses. These genes were not found in this study, which may be due to the expression specificity of lncRNAs in different horse breeds [27] and different omics levels, since TBX3, under strong selection in Chinese ponies, was also identified in this study.…”
Section: Discussionmentioning
confidence: 98%
“…As a core transcription factor in embryonic stem cells, ZNF281 (zinc finger protein 281) was found to be related to spontaneous osteochondrogenic differentiation [38]. Other studies showed the strong association of LCORL/NCAPG, HMGA2, PROP1, LASP [39], ZFAT, DIAPH3 [40], ACTN2, ADAMTS17, GH1, ANKRD1 [40], and ACAN [41,42] with miniature size and dwarfism in a variety of pony breeds, including Shetland [41,43], miniature [44], Welsh ponies [45], German warmblood horses [46], American miniature horses, Brazilian ponies [47], and Jeju ponies [48], as well as B4GALT7 [49] and PROP1 [50] in Friesian horses. These genes were not found in this study, which may be due to the expression specificity of lncRNAs in different horse breeds [27] and different omics levels, since TBX3, under strong selection in Chinese ponies, was also identified in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Putative causal variants in coding regions have been identified for simple, Mendelian diseases in the horse such as hyperkalemic periodic paralysis (Ptacek et al 1994), hereditary equine regional dermal asthenia (Tryon et al 2007) and dwarfism in Frisian horses (Leegwater et al 2016). However, complex inherited diseases, such as fracture risk (Blott et al 2014), osteochondrosis (van Grevenhof et al 2009; Lykkjen et al 2010; Teyssedre et al 2012; McCoy et al 2016) and recurrent laryngeal neuropathy (Dupuis et al 2011) have failed to be localized to coding regions of the genome despite extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Leegwater et al . () described a splice site mutation in beta‐1, 4 galactosyltransferase 7 ( B4GALT7 ), causing disproportionate dwarfism among Fresian horses, that also had a recessive mode of inheritance. In other species, variants in at least 14 genes have been reported to cause conditions characterized as dwarfism (reviewed in Boegheim et al .…”
Section: Introductionmentioning
confidence: 99%